Poxvirus membrane biogenesis: rupture not disruption - Krijnse-Locker, Jacomine; Sachsenheimer, Timo; Brügger, Britta (Cellular microbiology, 2013)
Enveloped viruses acquire their membrane from the host by budding at, or wrapping by, cellular membranes. Transmission electron microscopy (TEM) images, however, suggested that the prototype member of the poxviridae, vaccinia virus (VACV), may create its membrane ‘de novo’ with free open ends exposed in the cytosol. Within the frame of the German-wide priority programme we re-addressed the biogenesis and origin of the VACV membrane using electron tomography (ET), cryo-EM and lipid analysis of purified VACV using mass spectrometry (MS). This review discussed how our data led to a model of unconventional membrane biogenesis involving membrane rupture and the generation of a single open membrane from open membrane intermediates. Lipid analyses of purified virus by MS suggest an ER origin with a relatively low cholesterol content compared with whole cells, confirming published data. Unlike previous reports using thin-layer chromatography, no depletion of phosphatidylethanolamine was detected. We did detect, however, an enrichment for phosphatidic acid, diacylglycerol and phosphatidylinositol in the virion. Our data are discussed in the light of other pathogens that may requirecellular membrane rupture during their intracellular life cycle.
First published: 16 December 2012
Gesehen am 21.06.2018